К вопросу о развитии рогов у некоторых жвачных - Короткевич, Е.Л. (Вестник зоологии, 1980)
Homologous characters of the primary and secondary horns of the ruminants mentioned below are found on the basis of studies in the skulls of fossil and modern deer and giralfes. An assumption is advanced that the alteration of horns in deer cannot be considered their distinctive feature from giraffes. The finding of a one-horned samoterium skull has given rise to suppose that the primary horn formations alter in giraffes and deer at a certain stage of their evolutionary development.